2021
DOI: 10.51470/plantarchives.2021.v21.no2.040
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Physiology and Yield Responses of Four Rock Melon (Cucumis Melo Var. Cantaloupensis) Cultivars in Elevated Temperature

Abstract: Rock melon is a high value greenhouse crop. Reduction of economical crop yield in high temperature stress due to global warming is an emerging issue with Rock melon. Therefore, this study was conducted for evaluate the growth, physiology and yield of different Rock melon cultivars grown under high temperature stress. Four cultivars of rock melon (Lady-gold, Lady-green, Himalai-99 and Glamour) were evaluated for their physiological behaviors under two temperature (42±3°C and 47 ±3°C) regimes. In four cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It was reported that cantaloupe can tolerate in higher temperature than 45 °C. Heat stress due to high temperature throughout the cropping season decline biomass production, plant physiological and biochemical processes and finally, crop yield (39,17,3). Reactive oxygen species (ROS) produce when plants opened to heat stress conditions (5,15).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%
“…It was reported that cantaloupe can tolerate in higher temperature than 45 °C. Heat stress due to high temperature throughout the cropping season decline biomass production, plant physiological and biochemical processes and finally, crop yield (39,17,3). Reactive oxygen species (ROS) produce when plants opened to heat stress conditions (5,15).…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%
“…Melon is a tropical plant, and there are reports that plant development is impaired at temperatures below 12°C and above 40°C. Temperatures above 35°C interfere with the photosynthetic rate, and when temperatures reach 40°C, there is an increase in the respiration rate, which interferes with stomatal opening and closing and causes flower and fruit abortion (Amarasinghe et al, 2021). However, Jiménez et al (2001) showed that the melon plant can withstand temperatures above 40°C without affecting productivity when subjected to agrotextile use in the initial phase due to the porosity of the mesh, where gas exchange occurs between the internal and external environments.…”
Section: Microclimate Variablesmentioning
confidence: 99%
“…In addition, it has exhibited a hepato-protective effect activity against hypothyroidism and immunemodulating properties (Vella et al, 2019). Some genotypes of rock melon had higher stability and adaptability, including other promising traits to breed (Oliveira et al, 2019;Amarasinghe et al, 2021). Moreover, it adapts to extremely high temperatures (42 °C) and produces standard fruit quality (Amarasinghe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some genotypes of rock melon had higher stability and adaptability, including other promising traits to breed (Oliveira et al, 2019;Amarasinghe et al, 2021). Moreover, it adapts to extremely high temperatures (42 °C) and produces standard fruit quality (Amarasinghe et al, 2021). The genetic variation in segregating populations of rock melon is the key to breeding a desired cultivar for specific aims, such as, a larger fruit with high sugar content for restaurant necessities, food processing industry needs, and large families.…”
Section: Introductionmentioning
confidence: 99%